A PROPOSED METHOD TO EVALUATE COUNTRY’S ENERGY UTILIZATION EFFICIENCY - MIFTAHUL HUDA; NINING S. NINGRUM; RIDWAN SALEH (Puslitbang tekMIRA, 2012)
The threat of global warming should be addressed by increasing energy effi ciency and reducing energy consump- tion, since the green house gas mainly comes from combustion of fossil fuel in energy sector. Unfortunately, the conventional energy effi ciency indicator in national level such as energy consumption per capita (ECPC), energy intensity (energy consumption: gross domestic product (GDP)) and energy elasticity frequently shows a contradictory result. Energy consumption depends on both number of populations and GDP. Therefore, the energy effi ciency indicator should also consider both parameters. The objective of this study is to develop a new energy effi ciency indicator using both GDP and energy consumption per capita as parameters. In this study, a new energy effi ciency indicator namely A/R energy is proposed. A/R energy (addition or reduction of energy) is calculated by subtracting the value of best practice ECPC with the value of actual ECPC. The value of best practice ECPC was derived from an equation correlated between ECPC and Gross Domestic Product (GDP) per capita. Using the new indicator, it is revealed that some country with low ECPC in Africa, Asia and South America should increase their ECPC while all the developed country should reduce their ECPC. The best practice correlation between best practice ECPC and GDP per capita was also used to evaluate energy projection of Indonesia. Indonesia energy projection has been developed by IEA, Green Peace and Indonesian Government. Considering GDP and population growth ECPC, it is concluded that Indonesia energy projection developed by IEA is the most realistic, effi cient but achievable.